Bhakti poetry and Narendra Modi’s Hindu fascist pedagogy - Chakraborty, Kaustav (Politics, religion & ideology, 2025)
The article is an attempt to understand how the bhakti worldview has been politically misused to strengthen a political authoritarian cult of Modi in India. Bhakti has often been described as a love-based philosophy of devotedness, wherein, founded on faith-based loyalty, devotees cling to the personal, preferred deity and, following the footsteps of the mystics, aspire for complete self-forgetfulness while granting totalitarian power to the deity whom they treat as a guru-god. This article, through a critical textual analysis of the bhakti verses and songs composed by the bhakti poets, tries to expose the ways of misappropriation that the Hindu fascist Modi-cult has accomplished by politically coopting the transcendental bhakti renditions of the mystic poets. The calculated transmuting of the elements of bhakti spirituality for materialising political gains is the pathography of bhakti that this article wants to elucidate. The commonsensical projection of bhakti poetry, which has its major impact on the bhakta mass rather than the transcendental inner connotations, may easily provide validation to the propagations carried out by a Hindu fascist like Modi. This article tries to show that apparently benign ideologies can also be doctored to deploy them as weapons for hardening a divisive, fascist political cult.